Caring for carers: Understanding the physical and psychological well‐being of carers of veterans in Australia. (28th May 2021) - Post, Dannielle; van Agteren, Joep; Kasai, Daiki; Barrett, Alison; Doyle, Matthew; Kernot, Jocelyn; Baker, Amy; Parfitt, Gaynor
Abstract: Carers of veterans tend to put their own physical and psychological well‐being needs behind the needs of the person they are caring for and often do not seek assistance for their own physical and psychological well‐being. Combined, these factors lead to increased risk of acute and chronic illness and mental health issues. It is acknowledged that physical activity independently contributes to improved physical and mental health and may be a driver for mental well‐being in carers. The aim of this pilot research was to understand how movement behaviour and health behaviours of carers of veterans in Australia relate to carers' physical and psychological well‐being. Assessment occurred between February and July 2019 and included objective, validated measures to examine physical and psychological well‐being. To assess the association between physical and psychological factors, correlational analyses were performed. Twenty‐eight carers participated in the pilot study (96% female, mean age 61.6 years). Exercise capacity varied, and 84% of carers met the recommended 150 min of physical activity per week, with carers spending 8.6% of their time in moderate‐to‐vigorous physical activity; and 37.9% of the day sedentary. Psychological health outcomes reflect a population with high distress levels and lower than average mental well‐being, but with normal resilience scores. Carers with higher levels of resilience had greater exercise capacity, covering further distance in the 6‐min walk test, and as resilience increased, number of sedentary bouts decreased. This research demonstrates that there is a relationship between health behaviours and psychological well‐being in carers of veterans and serving personnel. Based on the findings of this pilot study, programmes to support family carers should include information about physical activity, reducing sedentary time, and increasing resilience. Interventions designed to improve physical and psychological well‐being should be trialled and evaluated for effectiveness.